A review on hydraulic conductivity and compressibility of peat - Wong, L.S.; Hashim, Roslan; Ali, F.H. (2009)
This study reviews the results of several experimental and field investigations on the behavior of peat in hydraulic conductivity and compressibility. A study on the mechanical properties of peat is important in order to gather sufficient information on the response of the soil to preloading in terms of the soil permeability and deformation. Preloading technique is normally employed as a method to improve peat ground so that the improved ground can be used as a soil foundation to support road embankment. Findings on the initial hydraulic conductivity of peat revealed that the initial coefficient of vertical permeability (kv0) of the soil ranged from 10-5 to 10-8 m sec-1 with the value was found to be lower in amorphous peat as compared to that of fibrous peat. Such findings indicated that the initial hydraulic conductivity of peat is influenced by the soil degree of decomposition. The higher is the soil degree of decomposition, the lower is its initial rate of hydraulic conductivity. Results from oedometer tests on Portage peat showed that while the soil coefficient of secondary compression (cÎ±1) ranged from 0.17 to 0.18, its coefficient of tertiary compression (cÎ±2) varied from 0.6 to 0.18. At high consolidation pressure, the soil cÎ±1 approached its cÎ±2 indicating the merging of secondary and tertiary compression components. It can be concluded that the behavior of peat is different from that of inorganic soil in that it exhibited high to moderate initial hydraulic conductivity, rapid primary consolidation and large secondary compression.